Nerve Injury Complicating Ultrasound/Electrostimulation-Guided Supraclavicular Brachial Plexus Block. Issue 4 (1st June 2010) - Reiss, Wojciech; Kurapati, Sushmitha; Shariat, Ali; Hadzic, Admir
Abstract : Background and Objectives: Neurologic complications after peripheral nerve blocks (PNBs) are relatively uncommon. It has been postulated that real-time, needle-nerve visualization during ultrasound-guided PNBs might further reduce the risk of neurologic or vascular complications. Case Report: In this report, we describe the occurrence of a severe brachial plexus injury after combined ultrasound and nerve stimulator-guided supraclavicular brachial plexus block. Conclusions: Ultrasound guidance should not preclude development of additional monitoring and protocols to decrease the risk of complications with PNBs.